1975
DOI: 10.1002/pssa.2210310249
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the dislocation distribution on the electrical resistivity in deformed metals

Abstract: s 70th birthdayThe effective resistivity is calculated for a simple cell structure by means of the Boltzmann equation. I n less heavily deformed metals the cell structure has only a negligible effect on the residual resistivity. In heavily deformed metals the observed DMR is in the same order of magnitude as that arising from the presence of the cell structure. Oleo decreases with increasing amount of cold work and this experimental result suggests that the DMR arising from the anisotropic dislocation scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The categorization of lattice defect types indicates that the most important source of strain broadening is dislocations. The effect of the strain field of dislocations was discussed in detail by Krivoglaz and Ryaboshapka [1963], Wilkens [1970], Krivoglaz et al [1983], Gaál [1984], Groma et al [1988] and Groma [1998]. Wilkens [1970] has shown that the higher order terms in the series expansion can be approximated by a second order expression by rescaling the length dependence of the deformation field of dislocations.…”
Section: Series Expansion Of the Fourier Coefficients Of Lattice Dist...mentioning
confidence: 99%
“…The categorization of lattice defect types indicates that the most important source of strain broadening is dislocations. The effect of the strain field of dislocations was discussed in detail by Krivoglaz and Ryaboshapka [1963], Wilkens [1970], Krivoglaz et al [1983], Gaál [1984], Groma et al [1988] and Groma [1998]. Wilkens [1970] has shown that the higher order terms in the series expansion can be approximated by a second order expression by rescaling the length dependence of the deformation field of dislocations.…”
Section: Series Expansion Of the Fourier Coefficients Of Lattice Dist...mentioning
confidence: 99%
“…(22) and (23) in [29]. For small values of K the Wilkens function can be approximated by a logarithmic function [6,11,12]:…”
Section: Fundamental Equationsmentioning
confidence: 99%
“…The following five or six fitting parameters are used: (i) m and (ii) V, the median and the variance of the log-normal size distribution density function in the size profile, (iii) U and (iv) M, the density and the arrangement parameter of dislocations in the strain profile and (v) q or q 1 and q 2 for the average dislocation contrast factors as in eqs. (6) or (7) for cubic or hexagonal crystals, respectively. The values of C h00 or C hk0 are not fitting parameters since they are only multiplicative factors in the Fourier coefficients of the strain profiles.…”
Section: The Fitting Procedures [30]mentioning
confidence: 99%
See 2 more Smart Citations